Evaluasi Pendidikan dalam Konteks Aspek Politik, Etika dan Interpersonal - Linda Wastri; Saadah, Nailis; Zulmuqim, Zulmuqim (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
The evaluation of educational programs is designed to identify improvements needed in the education system. In practice, program evaluation also involves political dimensions that should be a concern for both evaluators and the parties being evaluated. Furthermore, the relationship between morality and individuals is also an integral part of the ethical code used in the assessment. This article aims to explain the importance of ethical and political aspects in the implementation of educational program evaluation. The research method used is a literature review in which the author gathers information related to the ethical and political aspects when evaluating educational programs. Research findings indicate that several factors influence the relationship between ethics and individuals in educational assessment, including religious beliefs, moral values embedded in culture, treatment by the educational community, messages conveyed through mass media, and environmental conditions